Hannibal : Rome's greatest enemy - Freeman, Philip, 1961- (Pegasus Books, 2022)
"Over two thousand years ago one of the greatest military leaders in history almost destroyed Rome. Hannibal, a daring African general from the city of Carthage, led an army of warriors and battle elephants over the snowy Alps to invade the very heart of Rome's growing empire. But what kind of person would dare to face the most relentless imperial power of the ancient world? How could Hannibal, consistently outnumbered and always deep in enemy territory, win battle after battle until he held the very fate of Rome within his grasp?"--